Clinical utility of endocrine markers predicting myocardial siderosis in transfusion dependent thalassemia major. Issue 10 (12th June 2018) - Ehsan, Lubaina; Rashid, Mariam; Alvi, Najveen; Awais, Khadija; Nadeem, Omair; Asghar, Aleezay; Sajjad, Fatimah; Fatima, Malika; Qidwai, Asim; Hussain, Shabneez; Hasan, Erum; Brown, Nick; et al.
Abstract: Background: Endocrinopathy due to iron overload is the most common morbidity whereas myocardial siderosis causing toxic cardiomyopathy is the leading cause of mortality among patients with transfusion dependent thalassemia major (TDTM). If detected early, this can be treated with aggressive chelation. T2* cardiac magnetic resonance imaging (CMR) guided chelation protocols are now the gold standard but have limited availability in low and middle‐income countries. We hypothesized that markers of endocrine dysfunction would correlate with T2* CMR and can be used to predict the severity of myocardial siderosis and guide chelation therapy. Methodology: We undertook a multicenter retrospective study of 280 patients with TDTM to assess the prevalence of endocrinopathies and the predictive value of a number of individual and composite markers of endocrinopathy with T2* CMR. Results: The prevalence of hypogonadism, stunting, hypoparathyroidism, and hypothyroidism was 82%, 69%, 40%, and 30%, respectively. The sensitivity of hypogonadism and stunting predicting severe myocardial siderosis was 90% and 80%, respectively. Conclusion: We conclude that clinical markers of endocrine dysfunction, especially hypogonadism (positive likelihood ratio [LR+] = 1.4, 95% confidence interval [CI] = 1.0–1.9; positive predictive value [PPV] = 77%, 95% CI = 70–82; negative predictive value [NPV] = 57%, 95% CI = 34–77] and stunting (LR+ = 1.3, 95% CI = 1.1–1.6; PPV = 64%, 95% CI = 60–69; NPV = 55%, 95% CI = 45–64) in TDTM can predict severe myocardial siderosis and can potentially guide chelation therapy, especially where access to T2* CMR is limited.